Analisis Marjin Harga Beras pada Setiap Tingkat Rantai Pasok di Pulau Jawa: Analysis of Rice Price Margins at Each Supply Chain Levels on Java Island - Rachmadhan, Aditya Arief; Wijayati, Prasmita Dian (Jurnal Ilmiah Manajemen Agribisnis, 2024)
This study examines rice price margins on the island of Java at each level of the supply chain, including producers, wholesalers, and retailers. The method used in this research compares rice prices across six provinces on Java Island: (1) DKI Jakarta, (2) Banten, (3) West Java, (4) Central Java, (5) Yogyakarta, and (6) East Java. The data utilized consists of rice prices (Rp/kg) of all quality levels, sourced from the National Strategic Food Price Information Center (PIHPS) in October 2024. The study conducts descriptive analytical analysis by calculating the differences between: (1) producer (farmer) prices → wholesaler prices, (2) wholesaler prices → traditional market retailer prices, and (3) wholesaler prices → modern market retailer prices. The findings indicate variations in rice prices at each level of the supply chain on Java Island, from the producer to the retailer level, in both traditional and modern markets. Additionally, the varying price margins at each stage of the supply chain reveal differences in distribution efficiency and diverse cost structures among the provinces on Java Island.